2015
DOI: 10.1152/ajpcell.00141.2014
|View full text |Cite
|
Sign up to set email alerts
|

CaV3.2 T-type Ca2+ channels in H2S-mediated hypoxic response of the carotid body

Abstract: Arterial blood O2 levels are detected by specialized sensory organs called carotid bodies. Voltage-gated Ca(2+) channels (VGCCs) are important for carotid body O2 sensing. Given that T-type VGCCs contribute to nociceptive sensation, we hypothesized that they participate in carotid body O2 sensing. The rat carotid body expresses high levels of mRNA encoding the α1H-subunit, and α1H protein is localized to glomus cells, the primary O2-sensing cells in the chemoreceptor tissue, suggesting that CaV3.2 is the major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 32 publications
2
21
0
Order By: Relevance
“…Hypoxia induces Ca 2+ -dependent release of catecholamines (CAs) in glomus cells of the carotid body, an organ sensing arterial blood O 2 concentration, which is essential for controlling the function of respiratory and cardiovascular systems [22] . The hypoxia-induced secretion of CAs is observed also in the adrenal medullary chromaffin cells [52] .…”
Section: Involvement Of the H 2 S/ca V 32 Pathway In The Hypoxia-indmentioning
confidence: 99%
“…Hypoxia induces Ca 2+ -dependent release of catecholamines (CAs) in glomus cells of the carotid body, an organ sensing arterial blood O 2 concentration, which is essential for controlling the function of respiratory and cardiovascular systems [22] . The hypoxia-induced secretion of CAs is observed also in the adrenal medullary chromaffin cells [52] .…”
Section: Involvement Of the H 2 S/ca V 32 Pathway In The Hypoxia-indmentioning
confidence: 99%
“…However, people living at sea level most often experience intermittent hypoxia (IH) as a consequence of sleep apnea (i.e., brief, repetitive cessation of breathing) (22). IH, mimicking O 2 profiles encountered during sleep apnea, affects various cellular functions including activation of early genes (31), hypoxia-inducible factor (HIF)-1␣ (33), and voltage-gated Ca 2ϩ channels (14). Sleep apnea patients and IH-exposed rodents exhibit cardiovascular abnormalities, including hypertension and cardiac arrhythmias (18,30).…”
mentioning
confidence: 99%
“…The protocols for recording sensory nerve activity from ex vivo carotid bodies from mice were essentially the same as described previously (Makarenko et al 2015). Briefly, the carotid body with the sinus nerve was placed in a recording chamber (250 l vol) and superfused at a rate of 2.5 ml/min with warm (36°C) physiological saline (in mM: 125 NaCl, 5 KCl, 1.8 CaCl 2 , 2 MgSO 4 , 1.2 NaH 2 PO 4 , 25 NaHCO 3 , 10 D-glucose, and 5 sucrose).…”
Section: Methodsmentioning
confidence: 99%
“…We recently reported that low-threshold T-type VGCC, especially the CaV3.2, plays an equally important role in mediating hypoxia-induced Ca 2ϩ influx in glomus cells (Makarenko et al 2015). In the present study, we examined the effects of CIH on the glomus cell [Ca 2ϩ ] i response to hypoxia and assessed the role of VGCC.…”
mentioning
confidence: 89%
See 1 more Smart Citation